2019
DOI: 10.2138/gselements.15.4.241
|View full text |Cite
|
Sign up to set email alerts
|

How Plants Enhance Weathering and How Weathering is Important to Plants

Abstract: Since land plants emerged from swampy coastlines over 400 million years ago, they have played a fundamental role in shaping the Earth system. Roots and associated fungi increase rock weathering rates, providing access to nutrients, while altering atmospheric CO2. As soils weather, the dissolution of primary minerals forces plants to rely on recycling and atmospheric deposition of rock-derived nutrients. Thus, for many terrestrial ecosystems, weathering ultimately constrains primary production (carbon uptake) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…We found that vellozioid roots were prevalent in rock‐dwelling species and rhizosheaths in soil‐dwelling species, indicating that habitat specialization is associated with root morphological and physiological differentiation. The ability of the Velloziaceae to grow on bare rocks accelerates soil formation, releases rock‐derived nutrients to the ecosystem and allows, in the long term, the establishment of other species (Porder, ). We only observed dark‐septate fungi in roots of soil‐dwelling species, probably related to the greater amount of organic N in soil.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that vellozioid roots were prevalent in rock‐dwelling species and rhizosheaths in soil‐dwelling species, indicating that habitat specialization is associated with root morphological and physiological differentiation. The ability of the Velloziaceae to grow on bare rocks accelerates soil formation, releases rock‐derived nutrients to the ecosystem and allows, in the long term, the establishment of other species (Porder, ). We only observed dark‐septate fungi in roots of soil‐dwelling species, probably related to the greater amount of organic N in soil.…”
Section: Discussionmentioning
confidence: 99%
“…Vellozioid roots appear essential to grow on rocks due to their capacity to penetrate the rock matrix by dissolving the quartzite (Teodoro et al, ). The ability of these species to settle in rocky habitats by dissolving rocks by root‐exuded carboxylates increases the porosity of rocks and accelerates soil formation (Kelly, Chadwick, & Hilinski, ; Porder, ; Thiry, Fernandes, Milnes, & Raynal, ). These plants can therefore contribute to weathering and soil formation within rock cracks and the mobilization of nutrients from the rock, rendering them available in the future to other organisms, and slowly creating new microhabitats for plant establishment (Alves & Kolbek, ; Jacobi et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies along a Hawaiian chronosequence (soils of variable discrete initial formation age) have evaluated the role of soil age in weathering and the distribution and cycling of cations through plants. These studies revealed the dependency of nutrient cycling on the degree of weathering (e.g., Bullen and Chadwick, 2016;Chadwick et al, 1999;Laliberte et al, 2013;Porder and Chadwick, 2009;Vitousek, 2004). Studies along a climosequence (gradients in climate while minimizing other environmental differences) have evaluated the effect of climate on ecological and pedogenic processes (Bullen and Chadwick, 2016;Calmels et al, 2014;Dere et al, 2013;Egli et al, 2003;Ferrier et al, 2012).…”
Section: Introductionmentioning
confidence: 99%